Persepsi Mahasiswa PAI tentang Konsep Mahabbah terhadap Hidup Selibat dalam Perspektif Rabi’ah Al-Adawiyah - Syahrani, Annuriah; Darwis, Darwis; Muliyandari, Atika (Faculty of Education and Teacher Training of UINSI Samarinda, 2024)
Abstract The Mahabbah notion originated with the first female Sufi figure, Rabi'ah Al-Adawiyah. Sufism's teachings were one of Rabi'ah's reasons for not marrying. The figure of Rabi'ah, as well as the concept of mahabbah and Rabi'ah's life story, have been known in various parts of the world in Islamic history, including among Islamic Religious Education students at the Sultan Aji Muhammad Idris State Islamic University of Samarinda, where the researcher initially obtained answers by observing the students' daily lives. The pupil recognized Rabi'ah's figure and even idolized him through his love poetry to Allah. So the researcher's goal in this study is to investigate the perspectives of Islamic Religious Education Students at Sultan Aji Muhammad Idris Samarinda State Islamic University regarding the concept of Mahabbah Rabi'ah Al-Adawiyah. This study followed a qualitative descriptive research design. According to the findings of this study, students of Islamic Religious Education at Sultan Aji Muhammad Idris Samarinda State Islamic University have a harmonious perception that the concept of mahabbah is the perfect reason for someone to live celibate, owing to their understanding of mahabbah, specifically how pure a servant's love is for his Rabb. Celibacy, according to them, is defined as someone who chooses to live without marriage in order to improve their religion. However, a number of students stressed the importance of remembering the level of maqamat. Rabi'ah Al-Adawiyah's maqam is a guardian, therefore he is not reckless with his decisions, so lay people must exercise caution if they desire to be celibate while adhering to the notion of mahabbah, because his maqam is not present, allowing the concept of mahabbah to be broken. As a result, when studying Sufism, students must have a more in-depth and meaningful understanding. Keywords: Celibacy, Mahabbah, Rabi'ah Al-Adawiyah, Abstrak Konsep Mahabbah merupakan ajaran tasawuf dari tokoh sufi perempuan pertama, Rabi’ah Al-Adawiyah. Yang mana ajaran tasawufnya tersebut menjadi salah satu alasan Rabi’ah untuk hidup tanpa pernikahan. Sosok Rabi’ah beserta konsep mahabbah, dan kisah hidup Rabi’ah telah dikenal diberbagai belahan dunia dalam sejarah Islam, termasuk dikalangan mahasiswa Pendidikan Agama Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, dimana pada observasi awal peneliti memperoleh jawaban dari mengamati keseharian mahasiswa yang menggambarkan bahwa mahasiswa tersebut mengenali akan sosok Rabi’ah bahkan mengidolakannya melalui syair-syair cintanya kepada Allah. Maka tujuan dari penelitian ini adalah, peneliti ingin mengkaji terkait Persepsi Mahasiswa Pendidikan Agama Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda Tentang Konsep Mahabbah Rabi’ah Al-Adawiyah. Penelitian ini disusun dengan penelitian deskriptif kualitatif. Hasil dari penelitian ini ialah mahasiswa Pendidikan Agama Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda memberikan persepsi yang selaras bahwa konsep mahabbah adalah alasan yang sempurna jika seseorang ingin hidup selibat, karena pengetahuan mereka tentang konsep mahabbah yaitu bagaimana kemurnian cinta seorang hamba kepada Rabb-Nya. Adapun selibat dalam pandangan mereka yaitu seseorang yang memutuskan hidup tanpa pernikahan dengan tujuan untuk menyempurnakan agamanya. Namun, sejumlah mahasiswa juga menyampaikan pandangannya bahwa perlu diingat terkait tingkatan maqamat. Rabi’ah Al-Adawiyah maqamnya adalah wali sehingga tidak sembarangan dengan keputusannya, maka perlu berhati-hati bagi para awam jika ingin berselibat meskipun dengan konsep mahabbah, karena maqamnya tidak sampai sehingga konsep mahabbahnya bisa terpatahkan. Maka dari itu mahasiswa harus diberikan pemahaman yang lebih mendalam dan implikatif dalam mempelajari ilmu tasawuf. Kata Kunci: Mahabbah, Rabi’ah Al-Adawiyah, Selibat